Determinants of In-App Purchase Behavior in Augmented Reality Mobile Games: An Empirical Study of Pokémon Go Players in Indonesia - Indra Raga Cahyamukti; Utomo Sarjono Putro (Integrasi Sains Media, 2025)
In-app purchases (IAPs) are the primary revenue source for mobile games; however, sustaining player spending remains challenging, particularly in augmented reality (AR) games in emerging markets. While prior studies have examined IAP behavior in conventional mobile games, empirical evidence in AR contexts remains limited. This study investigates the determinants of in-app purchase intention among Pokémon GO players in Indonesia by integrating the Theory of Planned Behavior with expectation-confirmation and price fairness perspectives, while incorporating event design as a contextual factor. By positioning event design as a contextual antecedent within the Theory of Planned Behavior framework, this study extends prior TPB applications in mobile gaming by capturing how event-based features shape attitudinal and control-related evaluations in AR games. Data were collected via an online survey of 337 Indonesian players who had made at least one in-app purchase in the previous 12 months. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that attitude toward purchase is the strongest predictor of purchase intention, followed by perceived behavioral control and subjective norm. Event design and price fairness significantly influence attitude toward purchase, while event design also enhances perceived behavioral control. In contrast, expectation confirmation does not have a significant effect on attitude toward purchase. The findings highlight the importance of event-based value delivery and perceived fairness in sustaining monetization in AR mobile games.